Belgian guidelines for budget impact analyses. Issue 3 (June 2015) - Neyt, M.; Cleemput, I.; Sande, S. Van De; Thiry, N.
Abstract : Objectives: To develop methodological guidelines for budget impact analysis submitted to the Belgian health authorities as part of a reimbursement request. Methods: A review of the literature was performed and provided the basis for preliminary budget impact guidelines. These guidelines were improved after discussion with health economists from the Belgian Health Care Knowledge Centre (KCE) and different Belgian stakeholders from both government and industry. Preliminary guidelines were also discussed in a workshop with health economists from The German Institute for Quality and Efficiency in Healthcare. Finally, the guidelines were also externally validated by three external experts. Results: The guidelines give explicit guidance for the following components of a budget impact analysis: perspective of the evaluation, target population, comparator, costs, time horizon, modeling, handling uncertainty and discount rate. Special attention is given to handling varying target population sizes over time, applying a time horizon up to the steady state instead of short-term predictions, and similarities and differences between budget impact analysis and economic evaluations. Conclusion: The guidelines provide a framework for both researchers and assessors to set up budget impact analyses that are transparent, relevant, of high quality and apply a consistent methodology. This might improve the extent to which such evaluations can reliably and consistently be used in the reimbursement decision making process.